ANALISIS PENERIMAAN PAJAK SEBELUM DAN SESUDAH ADANYA INSENTIF PAJAK BAGI WAJIB PAJAK YANG TERDAMPAK COVID-19 SELAMA MASA PANDEMI PADA KPP PRATAMA MANADO - Wantasen, Meidiansjah Azhar; Sondakh, Jullie J.; Suwetja, I Gede (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
Tax revenues is expected to increase from year to year. In addition to the amount that consistently increases every year, taxes are also the largest source of state revenue. Therefore, it is important for taxpayers to always collect and deposit taxes into the state treasury in accordance with the provisions of the applicable minister of finance regulation plus incentives provided by the government as a from response to the Covid-19 pandemic. The researcher used qualitative descriptive method which aims to draw a conclusion from the data that has been collected. The results obtained that tax revenue at the Manado Tax Office decreased by 24% compared to the period before the tax incentive, and it was found that 1.570 taxpayers were applying for tax incentives and 227.882 taxpayers had been registered as recipients of tax incentives for the period from April to July 2020.